Comparative study of the gut microbial communities collected by scraping and swabbing in a fish model: a comprehensive guide to promote non-lethal procedures for gut microbial studies - Ruiz, Alberto; Torrecillas, Silvia; Kashinskaya, Elena; Andree, Karl B.; Solovyev, Mikhail; Gisbert, Enric (Frontiers in Veterinary Science, 2024)
In the present study, we propose the use of swabs in non-lethal sampling procedures to collect the mucosa-adhered gut microbiota from the posterior intestine of fish, and therefore, we compare the bacterial communities collected by conventional scraping and by swabbing methods. For this purpose, samples of the posterior intestine of rainbow trout (Oncorhynchus mykiss) were collected first using the swabbing approach, and after fish euthanasia, by mucosa scraping. Finally, bacterial communities were compared by 16S rRNA gene Illumina sequencing. Results from the current study revealed that similar values of bacterial richness and diversity were found for both sampling procedures. Similarly, there were no differences between procedures when using qualitative metrics (Jaccard and unweighted UniFrac) for estimating inter-individual diversity, but the quantitative metrics (Bray-Curtis and weighted UniFrac) showed a higher dispersion when samples were obtained by swabbing compared to scraping. In terms of bacterial composition, there were differences in abundance for the phyla Firmicutes and Proteobacteria. The cause of these differential abundances may be the inability of the swab to access to certain areas, such as the basal region of the intestinal villi. Moreover, swabbing allowed a higher representation of low abundant taxa, which may also have an important role in host microbiome regardless of their low abundance. Overall, our results demonstrate that the sampling method is a factor to be considered in experimental design when studying gut bacterial communities to avoid potential biases in the interpretation or comparison of results from different studies. In addition, the advantages and disadvantages of each procedure (swabbing vs scraping) are analyzed in detail, concluding that swabbing can be implemented as a reliable and non-lethal procedure for gut microbiota studies, which is of particular interest for animal welfare and the 3Rs principle, and may offer a wide range of novel applications.